What is special about silicon in functionalised organic semiconductors?. Issue 16 (16th July 2021) - Thorley, Karl J.; Benford, Micai; Song, Yang; Parkin, Sean R.; Risko, Chad; Anthony, John E.
Abstract : Atomic substitution in sidechains of an organic semiconductor show these solubilizing groups are not simple spectators. Silicon is the most electron withdrawing group 14 element, increasing photostability and offering desirable crystal packing. Abstract : A carbon side-chain analogue to the high-performance organic semiconductor triethylsilylethynyl difluoroanthradithiophene has been synthesised and characterized. Atomic substitution of carbon for silicon results in subtle changes to opto-electronic properties, which are rationalised by density functional theory and balance of electron donating and withdrawing effects. Larger differences are observed in photostability and solid-state packing of the new material in comparison to known silicon and germanium derivatives. Comparison of the group 14 elements teaches us about the newly synthesised system, but also how the silylethynyl substituents used for the last two decades contribute to successful employment of functionalised polycyclic aromatic hydrocarbons as organic semiconductors.